IMPLEMENTASI MEDIA INTERAKTIF BERBASIS MULTIMEDIA UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN PAI - Ahmad Adib Aziz; Devy Habibi Muhammad (Universitas Islam Negeri Sumatera Utara Medan, 2025)
Islamic Religious Education (PAI) learning at MA AL-UM Probolinggo faces challenges in increasing students' enthusiasm for learning due to the lack of variation in teaching methods. To overcome this, this study aims to analyze the implementation of multimedia-based interactive media in increasing students' motivation to learn. This study uses a qualitative descriptive approach method. Data were collected through observation, interviews, and documentation of teachers and students who use multimedia-based interactive media in PAI learning. The results of the study indicate that users of multimedia-based interactive media are able to increase students' interest and involvement in the learning process. Students are more enthusiastic in learning to understand PAI concepts because of the attractive visual, audio, and animation features. In addition, teachers can also more easily convey material dynamically and interactively. Thus, the implementation of multimedia-based interactive media can be an innovative solution to increase students' enthusiasm for learning at MA Al-Um Probolinggo. The recommendation from this study is further development in the form of a digital platform that can be accessed more widely to support learning effectiveness